ANALYSIS OF PAMSIMAS REVENUE FROM CLEAN WATER MANAGEMENT IN THE PERSPECTIVE OF MILK AD-DAULAH: : A Study in Abdya District, Indonesia - Faisal Fauzan; Ariq Azzaki (JURISTA: Jurnal Hukum dan Keadilan, 2022)
Gampong Padang Sikabu is one of the villages in Kuala Batee Sub-district, Southwest Aceh District that received the Pamsimas programme in 2017. Before the Pamsimas programme was built, the community used a spring water source that had to be taken to the foot of the mountain. The water quality was very clean, but the community had to collect it at the foot of the mountain and carry it home. After Pamsimas was built, the community can have water without having to fetch it at the foot of the mountain. However, the community also has to pay monthly fees to KPSPAMS members for the use of water from Pamsimas, from which Pamsimas bases its income and shares the proceeds with the gampong. To get the results of this study the author uses qualitative methods, this type of research is field research. The data collection techniques are observation, interview and documentation. The result of the research is that the clean water management system by Pamsimas and as well as the income obtained from the procurement of Pamsimas in Padang Sikabu Village is carried out with a deliberation system from all village traps, as well as the Milk Ad-Daulah concept of village water used for Pamsimas is also carried out by deliberation from all village traps, starting from the decree issued by the Keuchik, to the regulations that must be carried out together with the entire community, such as the rules for collecting bills and the time of collection. As for the practice / Results of Pamsimas Revenue from Clean Water Management by Padang Sikabu Village in the Perspective of Milk Ad-Daulah, it is carried out with several principles that are practiced, such as the principles of trust and trustworthiness, the principle of sharing profits from the Pamsimas business is also practiced and the principle of prudence in the management of Pamsimas is also practiced. While the opportunities and constraints of Pamsimas in profit sharing with Padang Sikabu Village include the support and trust of the village government, as well as the support and cooperation of the Padang Sikabu Village community.